A Unified Approach for the Assembly of Atisine‐ and Hetidine‐type Diterpenoid Alkaloids: Total Syntheses of Azitine and the Proposed Structure of Navirine C. (26th April 2018) - Liu, Jie; Ma, Dawei
Abstract: A tetracyclic dinitrile was synthesized in twelve steps from cyclohex‐2‐en‐1‐one by using a chelation‐triggered conjugate addition to a γ‐hydroxy‐substituted α, β‐unsaturated nitrile and an oxidative dearomatization/Diels–Alder cycloaddition cascade as the key steps. The first total synthesis of azitine (in 17 steps) was achieved through a simple reductive cyclization of this intermediate and subsequent transformations while the total synthesis of the proposed structure of navirine C (in 19 steps) was accomplished by a hydrogen‐atom‐transfer reaction of the tetracyclic dinitrile, Pd/C‐catalyzed reductive cyclization, and subsequent functional group manipulation. Abstract : Ein tetracyclisches Dinitril wurde über eine chelatgesteuerte konjugierte Addition an ein α, β‐ungesättigtes γ‐Hydroxynitril und eine oxidative Desaromatisierung/Diels‐Alder‐Cycloaddition in 12 Schritten aus Cyclohex‐2‐en‐1‐on synthetisiert. Es diente dann als gemeinsames Intermediat für Totalsynthesen von Azitin (17 Stufen) und der vorgeschlagenen Struktur von Navirin C (19 Stufen).